The Dr. Jekyll and Mr. Hyde complexity of the macrophage response in disease. Issue 2 (13th February 2017) - Twum, Danielle Y F; Burkard-Mandel, Lauren; Abrams, Scott I
Abstract : Review of concepts related to the complexity of macrophage biology, with emphasis on their origin and transcriptional cues that dictate their roles in disease. Abstract: Macrophages comprise a highly diverse cell population expressing a continuum of biologic activities dictated by exposure to a plethora of inflammatory cues. Moreover, in contrast to most other hematopoietic populations, macrophages can arise from multiple sites—namely, the bone marrow or yolk sac, adding to the complexity of macrophage biology during health and disease. Nonetheless, it is this very type of diversity that is indispensable for macrophages to respond effectively to pathologic insults. Most of the interest in macrophage biology has been devoted to bone marrow-derived populations, but it is now becoming clearer that tissue-resident populations, which arise from distinct hematopoietic compartments, serve critical roles in host defense, including protection against neoplastic disease. Depending on the inflammatory milieu, macrophages can behave as a "two-edged sword, " playing either host-protective (i.e., antitumor) or host-destructive (i.e., protumor) roles. Accordingly, we review herein the mechanisms that instruct macrophage functional diversity within their microenvironments, with special emphasis on transcriptional regulation, which is less understood. Given their polarizing positions in disease processes, we will also provide an overview of strategies that target macrophages or their effector mechanisms for therapeutic purposes.